Thermal, economic and environmental analysis of domestic solar water heaters in Malaysia / Fayaz Hussain - Hussain, Fayaz (2013)
Solar thermal utilization, especially the application of solar water heater technology, has developed rapidly in recent decades. Solar water heating systems are practical applications to replace the use of electrical water heaters. But the performance of these systems depends on weather and exhibit a nonlinear dependence. This makes it difficult to accurately analyze their performance by simply observing their response to short-term or average weather conditions. The purpose of this project is to show solar potential through contour mapping and do thermal, economic and environmental analysis of evacuated-tube, glazed and unglazed collector solar water heaters. The optimum performance of solar water heaters and their comparison among them is done to select right solar water heater according to the domestic hot water demands along with the calculations of resultant GHG reductions for the period of 20 years. Analysis showed that evacuated-tube, glazed and unglazed solar water heaters achieve solar fraction value of 1.0, 0.92 and 0.82 respectively. Evacuated-tube, glazed and unglazed solar water heaters show life cycle savings of 5200, 4730 and 4150 RM, and greenhouse gas reductions of 113,220, 104,162 and 99633 kg respectively. Optimal thermal performance is obtained by evacuated-tube solar water heater, which results in reduction of household greenhouse gas emissions, reduction of energy consumption and saves money on energy bills as compared to glazed and unglazed collector solar water heaters. Overall, all the types of solar water heaters give satisfactory performance thermally, economically and environmentally. Evacuated-tube collector solar water heater will serve the needs with maximum thermal output with extra liters of water without any auxiliary electric water heater installation and energy use. Glazed and unglazed collector solar water heaters will need extra installations of electric water heater and use of auxiliary energy, which in result increases the cost of equipment and auxiliary energy for heating purposes as compared to evacuated-tube collector solar water heater.